PERSEPSI ETNIS MADURA DALAM KEBERLANJUTAN PENDIDIKAN ANAK KEPERGURUAN TINGGI - Marsidi Marsidi; Rustiyarso Rustiyarso; Riama Alhidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The title of this research is "Madura Ethnic Persession in Continuing Education in Higher Education Children (Study in Wajok Hulu Village, Sianatan District)". The method used is descriptive method with a form of qualitative research. The data source of this research is the people who are in Wajok Hulu Village, Jalan Parit Baru, Siantan District. Data collection techniques in this study are through interviews, observation and documentation, while the data collection tools used are observation guides, interview guides and documentation tools. The analysis in this study was presented in a descriptive qualitative manner using 6 informants. The results of this study are: 1. Madura Ethnic Perception in Wajok Hulu Village in Continuing Education in Higher Education Children is good and very important, this is based on the Madurese Ethnics in Wajok Hulu Village, Jalan Parit Baru, Siantan District, already know that currently education is very prioritized especially in the field of work but also for the future of their children. 2. Ethnic Madura in Wajok Hulu Village, Jalan Parit Baru Siantan District, already know and see firsthand that graduates from their teacher faculties are becoming teachers in various schools. Keywords: Madura, Perception, Sustainability of Children's Education.